Marketing Strategy and Its Economic Implications on Consumer Loyalty: The Mediating Effect of Customer Satisfaction - Moh Rizky Maulana Sandy; Muh. Abdul Aziz; Muhammad Khairul Amal (International Journal of Economics Development Research (IJEDR), 2025)
This study investigates the effect of marketing factors on customer loyalty with customer satisfaction as a mediating variable among customers of Andita Medika Pharmacy in Sukabumi, Indonesia. The marketing factors examined include price perception, brand image, brand trust, and electronic service quality. A quantitative approach was employed using purposive sampling, involving 120 respondents. Data were collected through a seven-point Likert scale questionnaire and analyzed using Structural Equation Modeling (SEM) with AMOS version 26. The results reveal that price perception, brand image, brand trust, and electronic service quality have positive and significant effects on customer satisfaction. Furthermore, brand image, brand trust, electronic service quality, and customer satisfaction significantly influence customer loyalty. In contrast, price perception does not have a direct effect on customer loyalty, indicating that its impact is mediated by customer satisfaction. These findings emphasize the importance of strengthening brand-related factors and digital service quality to enhance customer satisfaction and foster long-term customer loyalty in the pharmaceutical retail industry.